2015
DOI: 10.1530/rep-14-0685
|View full text |Cite
|
Sign up to set email alerts
|

The role of WNT signaling in adult ovarian folliculogenesis

Abstract: Wingless-type mouse mammary tumor virus integration site (WNT) signaling molecules are locally secreted glycoproteins that play a role in a number of physiological and pathological developmental processes. Components of the WNT signaling pathway have been demonstrated to impact reproductive functions including embryonic development of the sex organs, and regulation of follicle maturation controlling steroidogenesis in the postnatal ovary. Emerging evidence underscores the complexity of WNT signaling molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 100 publications
0
58
0
Order By: Relevance
“…Wnt signaling regulates many developmental processes, including differentiation, proliferation, and apoptosis (Logan & Nusse, )—each of which is dynamically involved with corpus luteum function. Wnt ligands and Frizzled G receptor are expressed in developing follicles and corpora lutea of rats, mice, humans, and cattle (Hernandez Gifford, ; Hsieh, Johnson, Greenberg, & Richards, ). WNT2 and WNT4 in particular were extensively studied in the postnatal ovary, primarily by genetic manipulation of specific components of the Wnt pathway (Hernandez Gifford, ; Hsieh et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt signaling regulates many developmental processes, including differentiation, proliferation, and apoptosis (Logan & Nusse, )—each of which is dynamically involved with corpus luteum function. Wnt ligands and Frizzled G receptor are expressed in developing follicles and corpora lutea of rats, mice, humans, and cattle (Hernandez Gifford, ; Hsieh, Johnson, Greenberg, & Richards, ). WNT2 and WNT4 in particular were extensively studied in the postnatal ovary, primarily by genetic manipulation of specific components of the Wnt pathway (Hernandez Gifford, ; Hsieh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt ligands and Frizzled G receptor are expressed in developing follicles and corpora lutea of rats, mice, humans, and cattle (Hernandez Gifford, ; Hsieh, Johnson, Greenberg, & Richards, ). WNT2 and WNT4 in particular were extensively studied in the postnatal ovary, primarily by genetic manipulation of specific components of the Wnt pathway (Hernandez Gifford, ; Hsieh et al, ). Here, we used the small‐molecule inhibitor XAV939 to decrease total and nuclear β‐catenin content, thus affecting the activity of most canonical Wnt signaling in the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation of CpG islands harboring promoters is a strong indicator of suppressed gene expression, and we first investigated genes with known functions in fertility. We identified, and confirmed by targeted bisulfite sequencing ( Fig S1A), elevated methylation levels in CpG islands associated with FZD1 and RUNX3, both of which encode proteins that regulate ovarian folliculogenesis 18,19 , and also RASAL3, which controls a magnitude of inflammatory responses 20 and has been linked specifically to inflammatory bowel disease . Pathway analysis revealed that genes with differentially methylated CpGs were significantly enriched in the Hippo (FDR 6.99E-12) and PI3K-Akt (FDR 2.83E-07) signaling pathways ( Fig S1B-D), both of which play central roles in regulating follicle recruitment and growth 22,23 .…”
Section: Differential Methylation Patterns In Bangladeshi Women Who Gmentioning
confidence: 60%
“…The top 20 significant KEGG pathways identified in both exposure studies are similar to the findings based on GO BPs. In particular, the regulatory biological pathways linked to phenotypes, including neuroactive ligand-receptor interaction (relates to locomotion Inoki et al, 2016), wnt and MAPK signaling pathways (relates to reproduction and cell growth (Inoki et al, 2016;Hernandez Gifford, 2015;Zhang & Liu, 2002;Andrade et al, 2014)), were found to be downregulated in both experiments. The pathway interaction analysis by ClueGO showed that wnt signaling pathway was interacting with tgf-beta pathway which was also enriched with significantly negative NES in both toxicities.…”
Section: Discussionmentioning
confidence: 94%
“…Ribosome, proteasome, aminoacyl-tRNA biosynthesis and RNA transport were significantly upregulated in both groups, indicating overall higher rate of protein turnover upon exposure. In contrast, biological pathways reflecting phenotypes including neuroactive ligand-receptor interaction [regulating locomotion (Kong et al, 2015)], wnt-signaling (regulating reproduction and cell growth (Inoki et al, 2006;Hernandez Gifford, 2015) and MAPK signaling (regulating reproduction and cell growth (Zhang & Liu, 2002;Andrade et al, 2014) were significantly down-regulated in both exposures (Fig. 7).…”
Section: Resultsmentioning
confidence: 99%